Frederick Law Olmsted: a pragmatic exception to Transcendental writing. Issue 3 (2nd July 2020) - Ferguson, Benjamin
ABSTRACT: There has been a resurgence of interest in Frederick Law Olmsted's career, yet his landscape architecture tends to overshadow his travel writing. This article offers a re-appraisal of his literary oeuvre, which, in its often epistolary and direct style, along with his uniquely technical eye, may strongly resonate with a technology-focused twenty-first century that prizes pragmatic and journalistic writing on topics of social problem-solving. The article suggests that Olmsted's work serves as an important reference point for a strain of US travel writers whose work is similar to that of the nineteenth-century Transcendentalists in focusing on a shift away from Europe and toward finding identity – and perhaps "transcendence" – in American "wildness", but who can be seen as exceptions to that movement for their practical, often technocratic, approaches, as they mix their diverse careers with their travel writing.